Meta-analysis of randomized clinical trials comparing intraumbilical versus periumbilical incision in laparoscopic appendectomy - Mohr, Justyna; Probst, Pascal; Kalkum, Eva; Antony, Pia-Anita; Maurer, Katharina; Kleindienst, Dirk; Schnüriger, Beat; Hauswirth, Fabian; Müller, Markus K.; Renzulli, Pietro Alexander (World journal of surgery, 2025)
BackgroundLaparoscopic appendectomy has become the standard treatment for acute appendicitis. However, surgical site infections still occur in up to 8% of patients. The aim of this review was to compare the short- and long-term outcomes of an intraumbilical incision with a periumbilical incision for umbilical port placement in laparoscopic appendectomy.MethodsA systematic literature search for randomized clinical trials (RCTs) was performed in CENTRAL, PubMed, Embase, and Web of Science (last search 10 January 2025). Four outcome variables provided sufficient data to allow for a meta-analysis using the random-effects model. Risk of bias (Cochrane 2.0) and certainty of evidence (GRADE) were assessed.ResultsSix RCTs from Asia with 1576 patients were included. An intraumbilical incision may have little to no effect on operation time (MD -1.57 min, 95%-CI: -5.30 to 2.16, p = 0.41, I2 = 98%, and GRADE = very low) and length of hospital stay (MD 0.17 days, 95%-CI: -1.12 to 1.47, p = 0.79, I2 = 93%, and GRADE = very low). Moreover, the evidence suggests that an intraumbilical incision may result in little to no difference in internal organ injury (OR 0.69, 95%-CI: 0.33 to 1.43, p = 0.32, I2 = 0%, and GRADE = low) and umbilical surgical site infection (OR 0.76, 95%-CI: 0.40 to 1.44, p = 0.40, I2 = 22%, and GRADE = low). Five RCTs were assessed as having a high risk of bias, whereas one study raised some concerns.ConclusionsThe evidence suggests that there is little to no difference in any of the clinical short-term outcomes between intraumbilical and periumbilical port placement in laparoscopic appendectomy. Surgeons should use their preferred approach. The body of evidence would benefit from a high-quality RCT in a western population and from data on long-term outcomes. Trial Registration: CRD42025628000 (PROSPERO).ConclusionsThe evidence suggests that there is little to no difference in any of the clinical short-term outcomes between intraumbilical and periumbilical port placement in laparoscopic appendectomy. Surgeons should use their preferred approach. The body of evidence would benefit from a high-quality RCT in a western population and from data on long-term outcomes. Trial Registration: CRD42025628000 (PROSPERO).